A simple flame strategy for constructing W‐doped BiVO4 photoanodes with enhanced photoelectrochemical water splitting. (6th August 2020) - Yang, Yingchen; Zhao, Yong; Fan, Weiqiang; Shen, Hao; Shi, Weidong
Summary: Bismuth vanadate (BiVO4 ) with narrow band gap has been widely reported in photoelectrochemical (PEC) water splitting. However, the low kinetic of water splitting is still the key for limiting the PEC performance of BiVO4 . Herein, a W‐doped BiVO4 (W‐BVO) photoanode has been controllably prepared by a fast flame method within 40 seconds. The preparation condition including calcination time and quantity of W precursor has been systemically investigated, in order to optimize the PEC performance of W‐BVO. X‐ray photoelectron spectroscopy indicates that the introduction of W did not obviously cause the formation of oxygen vacancies, revealing that W has been doped into the crystal structure of BiVO4 by flame method. The electrochemical impedance spectroscopy further confirmed that the W‐BVO possesses a lower charge transfer resistance with fast transfer ability of carriers. Based on the incident photon‐to‐electron conversion efficiency, the acceptable solar to electron conversion efficiency of 5.79% (340 nm, 1.23 V vs RHE) has been achieved in the W‐BVO system. A PEC mechanism has been proposed to demonstrate the promotion of kinetic for PEC water splitting. This work offers a promising alternative route for the design and fabrication of efficient photoanodes in other PEC systems. Abstract : An ultra‐fast flame method was used to prepare W‐doping bismuth vanadate photoanode for enhancing the transport ability of carriers.